2018
DOI: 10.1007/s13205-018-1158-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of silver nanoparticles biosynthesis mediated by Aspergillus niger NRC1731 through application of statistical methods: enhancement and characterization

Abstract: The fungal-mediated silver nanoparticles (AgNPs) biosynthesis optimization via the application of central composite design (CCD) response surface to develop an effective ecofriendly and inexpensive green process was the aim of the current study. Nanosilver biosynthesis using the NRC1731 cell-free filtrate (CFF) was studied through involving the most parameters affecting the AgNPs green synthesis and its interactions effects. The statistical optimization models showed that using 59.37% of CFF in reaction contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…The size and high surface area of AgNPs play an important role by enabling them to reach easily the nuclear content of bacteria to exhibit relatively high antibacterial activity (Yurtluk et al, 2018). Similar reports have been documented by Elsayed et al (2018) and Sowmya et al (2019) suggested that + AgNPs exhibit antibacterial activity by releasing Ag ions, which gets attached to the surface of bacterial cell membrane and may disrupt membrane permeability, DNA replication, induce ROS and subsequently leading to bacterial cell death.…”
Section: X-raysupporting
confidence: 52%
“…The size and high surface area of AgNPs play an important role by enabling them to reach easily the nuclear content of bacteria to exhibit relatively high antibacterial activity (Yurtluk et al, 2018). Similar reports have been documented by Elsayed et al (2018) and Sowmya et al (2019) suggested that + AgNPs exhibit antibacterial activity by releasing Ag ions, which gets attached to the surface of bacterial cell membrane and may disrupt membrane permeability, DNA replication, induce ROS and subsequently leading to bacterial cell death.…”
Section: X-raysupporting
confidence: 52%
“…Production of AgNPs follows the equations described above. The reaction of synthesis can be confirmed by change in the color of the medium [71]. Several aspects as medium properties, incubation time and temperature, AgNO 3 and biomass concentrations and activity, are of crucial relevance.…”
Section: Green Chemistrymentioning
confidence: 90%
“…Based on analysis, its assumed that these biomolecules and proteins may be involved in the capping stabilization. IR spectra vary with the characteristics of the organism/specie used in the AgNPs synthesis [71].…”
Section: Characterization Of Agnpsmentioning
confidence: 99%
“…The application of new approaches such as synthesis optimization via statistical methods (such as central composite design and response surface methodology) has been proposed in a few studies and showed some promise but remains mostly unexplored [ 98 , 101 ]. Such approaches are expected to significantly reduce the number of different lab tests required and lead to a quicker optimization of MNP production, thus warranting a closer look.…”
Section: Discussionmentioning
confidence: 99%